Immiserizing Capital Flows to Developing Countries - Dieter Bender; Wilhelm Löwenstein (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2014)
Based on a neoclassical growth model for open low income economies this paper shows that development strategies, which rely on net borrowing abroad lead to a position of sustainable foreign indebtedness (provided that all capital imports are used for investment financing), but turn out to be immiserizing. The paper proves that development financing by foreign loans is either ineffective in terms of increasing per capita income but associated by sustainable foreign debts, or the effectiveness is bought at the price of growing into unsustainable debt positions. The first option is stable but counterproductive. The second option is effective but unstable.
Keywords: F34; F43; O41; 330; Immioserizing growth; Foreign debt; Low income countries; Entwicklungsfinanzierung; Kapitalimport; Internationale Staatsschulden; Verelendungswachstum; Theorie; Entwicklungsländer